Perempuan berdaya melawan korupsi: Studi kasus kader Posyandu Desa Rumpin dalam menyikapi politik uang - Mentari Anjhanie Ramadhianty; Usep Hasan Sadikin; Rizky Argama (Integritas: Jurnal Antikorupsi, 2023)
As a part of vulnerable groups contributing to a greater number of voters than men, women are prone to be targeted as the objects of money politics during the 2019 General Election (Pemilu) and 2020 Regional Election (Pilkada). The degree of vulnerability adds up when the Criminal Code (KUHP) and laws on Regional Election (UU Pilkada) put punishment upon the perpetrator and recipient of money politics. This research, done on the female cadres of the Durian Integrated Health Service Post (Posyandu) in Rumpin Village, Rumpin District, West Java, showcases that women’s empowerment in raising awareness and establishing relationships could calibrate the hegemony and the patriarchal structure in money politics. All the cadres in Durian Posyandu had experienced being the target of money politics. However, within the realization and relationship among women, money, goods, or public facilities from perpetrators of political parties or political allies could not affect women’s political choices. Within the open-list proportional electoral system and extreme multiparty system which systematically promote money politics, the advancement of women’s empowerment is necessary to shift money politics into ideological and visionary political transactions according to aspirations and policies to fulfill citizens' rights.